Glycemic Control, Lipid Profiles, and Cardiac Outcomes in Obese Patients with Ischemic Heart Disease. A Comparative Study - Muhammad Zahid Ali Raza, Aamir Siddique, Shaoib Ahmed Zia, Tayyab Mohyuddin, Arslan Aslam Chahudhary, Faiza Altaf (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Obesity is a well-established risk factor for ischemic heart disease (IHD), exerting its effects through insulin resistance, dyslipidemia, and systemic inflammation. South Asian populations demonstrate a higher cardiometabolic burden, yet limited data exist on the interplay between glycemic control, lipid abnormalities, and cardiac outcomes in obese IHD patients. Objective: To evaluate glycemic control, lipid profiles, and cardiac outcomes in obese patients with ischemic heart disease treated at two tertiary care hospitals in Pakistan. Methodology: A comparative cross-sectional study was conducted on 100 obese patients with IHD at Nawaz Sharif Medical College, Aziz Bhatti Shaheed Teaching Hospital, Gujrat, and Chahudhary Pervaiz Elahi Institute of Cardiology, Wazirabad, from January to June 2023. Demographics, glycemic indices (fasting plasma glucose, HbA1c), lipid parameters (total cholesterol, triglycerides, LDL-C, HDL-C), inflammatory markers (hs-CRP), and cardiac biomarkers (NT-pro BNP, hs-troponin I) were measured. Echocardiographic outcomes included left ventricular ejection fraction (LVEF) and diastolic function. Statistical analyses were performed using t-tests, chi-square tests, and multivariate logistic regression. Results: The cohort had a mean age of 56.8 ± 8.2 years with a male-to-female ratio of 1.2:1. Poor glycemic control was observed (HbA1c 7.9 ± 1.4%), with atherogenic dyslipidemia (TG 192.4 ± 46.8 mg/dL, LDL-C 136.7 ± 32.1 mg/dL, HDL-C 38.6 ± 8.2 mg/dL). Elevated hs-CRP, NT-pro BNP, and hs-troponin I were significantly associated with reduced LVEF (<45%) and diastolic dysfunction. Nearly one-third experienced acute coronary syndromes during the study period. Conclusion: Obese IHD patients exhibit poor metabolic and inflammatory profiles strongly linked to adverse cardiac outcomes. Comprehensive strategies targeting glycemic control, lipid optimization, and early biomarker-based risk assessment are essential for improving prognosis in this high-risk population. Keywords: Obesity, ischemic heart disease, glycemic control, lipid profile, cardiac biomarkers, South Asia.